Mapping the relationship between obesity and endometrial cancer: current research hotspots and future trends (2003-2024) - Liang, Lei; Song, Chuangxiu; Yang, Bo; Chang, Chun; Chen, Shichao; Sun, Li (Frontiers in Oncology, 2025)
BackgroundObesity is an independent risk factor for endometrial cancer (EC). Bibliometrics allows for the analysis of multiple data from published publications to identify the current state of research and future trends and to construct a knowledge framework. There is a lack of high-quality bibliometric analyses of obesity and EC.MethodsThis study retrieved publications related to obesity and EC from the Web of Science Core Collection (WOSCC) from 2003 to 2024. Publication trends were analyzed using Microsoft Excel 2019, while CiteSpace (v.6.4.R1 Advanced) was employed to analyze institutional co-occurrence, cited journals, journal co-citation mapping, co-cited references, and keywords. VOSviewer (v.1.6.20) was used to analyze the journals in which the publications appeared. SCImago Graphica (v.1.0.39) was utilized to investigate the distribution and collaboration of countries/regions, institutional collaborations, and author collaborations.Results681 publications from 2003 to 2024 were included in the final analysis. The volume of publications showed an upward trend, peaking in 2021. The United States was the country with the highest number of publications, with the National Cancer Institute (NCI) being the leading institution. Scholars Emma J. Crosbie and Faina Linkov had the highest publication counts, while CALLE EE was the most cited scholar. The journal Gynecologic Oncology (Q1/4.5) published the most relevant articles and was also the most frequently cited journal. The most common keywords were “endometrial cancer,” “body mass index,” and “risk.” Current research focuses on exploring the mechanisms linking obesity and EC and analyzing the impact of obesity on clinical treatment strategies for EC. Future research directions include: (1) expanding the scope to related diseases of EC; (2) emphasizing typical indicators and diagnostic techniques for EC; (3) developing new treatment methods and technologies to enhance clinical efficacy; and (4) further strengthening the exploration of the pathological mechanisms related to obesity and EC.ConclusionThis study comprehensively summarizes the knowledge structure of obesity and EC and identifies key research hotspots and trends. Based on our findings, the formation of a multidisciplinary team, the rational application of diagnostic and therapeutic techniques, the further enhancement of the exploration of the pathological mechanisms associated with obesity and EC as well as the improvement of clinical diagnostic and therapeutic strategies are powerful measures to promote the development of this field.